Fases lunares en la reproducción vegetativa de cacao (Theobroma cacao L.), Babahoyo, Ecuador - Víctor Molina Barbotó; Ricardo X. Chávez Betancourt; Darío Dueñas Alvarado (European Scientific Journal, ESJ, 2016)
Cacao is the third entry in agricultural exports in Ecuador. In addition, it represents the income for more than 100000 workers in Esmeralda, the Amazon, Los ríos, Guayas and Manabi. The increase demand of ecuadorian cacao is due to its unique characteristics. This cacao is use to make the most important dark chocolate in the world. In this study, we determined which lunar phase is the more adequate in vegetative reproduction by rooted cuttings. Ten treatments were used with National Cacao and CCN-51. Results suggest that full moon is the phase with more influence for producers.